2021
DOI: 10.1057/s41599-021-00799-6
|View full text |Cite
|
Sign up to set email alerts
|

Occupational gender segregation and gendered language in a language without gender: trends, variations, implications for social development in China

Abstract: This paper proposes a textual analytics approach to the discovery of trends and variations in social development. Specifically, we have designed a linguistic index that measures the marked usage of gendered modifiers in the Chinese language; this predicts the degree of occupational gender segregation by identifying the unbalanced distribution of males and females across occupations. The effectiveness of the linguistic index in modelling occupational gender segregation was confirmed through survey responses fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 65 publications
0
1
0
Order By: Relevance
“…Huang et al (2021) and Dong et al (2021) showed that the variations in the use of different linguistic devices to encode kinesis in China correspond to the actual distribution of weather patterns in China based on the different kinetic energy of the weather events. Su et al (2021) showed that historical and geographic variations in professional gender segregation in China can be mapped to the use (or lack) of gender modification of professional terms. Wang et al (2022) showed that the use of different speech act constructions pragmatically reflects the different social dynamics in two culturally different societies: Guangzhou and Hong Kong.…”
mentioning
confidence: 99%
“…Huang et al (2021) and Dong et al (2021) showed that the variations in the use of different linguistic devices to encode kinesis in China correspond to the actual distribution of weather patterns in China based on the different kinetic energy of the weather events. Su et al (2021) showed that historical and geographic variations in professional gender segregation in China can be mapped to the use (or lack) of gender modification of professional terms. Wang et al (2022) showed that the use of different speech act constructions pragmatically reflects the different social dynamics in two culturally different societies: Guangzhou and Hong Kong.…”
mentioning
confidence: 99%